Brand Association, Patient Experience, and Patient Involvement Improved Awareness of Re-visit to Hospital - Supriyati, Titin; Tahjoo, Anastina; Pamungkas, Rian Adi (Alta Dharma Publisher, 2025)
Background: Number of patient visits decreased from 2019 to 2020 by 31.18%. This encourages hospitals to implement a patient-oriented marketing concept and a comprehensive understanding of consumer behavior. One of the factors for a hospital's success is attracting patients to return. Factors that influence Return Visit Intention are Brand Association, Patient Engagement and Patient Experience. Objective: The purpose of this study is to empirically reveal the influence of brand association and patient experience on the interest in returning to the An-Nisa Hospital polyclinic in Tangerang with patient engagement as an intervening variable. Method: This study is included in quantitative research, the population used is patients who have visited at least 2 times, the sample calculation uses the indicator formula x 5, so that a sample of 190 respondents is obtained with a sampling technique using purposive sampling. The analysis method used is the three box method and SEM analysis. Result: The results of the analysis conclude that brand association, patient experience, and patient engagement have a significant effect on return visit interest. In addition, the results obtained are that brand association and patient experience have a significant effect on patient engagement. Patient engagement has been shown to be an intervening variable between brand association and patient experience on revisit intention. Conclusion: This study demonstrates that brand association, patient experience, and patient engagement are crucial factors influencing the intention of patients to revisit the An-Nisa Hospital polyclinic in Tangerang. Recommendation: These efforts will help the hospital build stronger relationships with its patients, encouraging loyalty and repeat visits, ultimately addressing the decline in patient numbers